RESPON TANAMAN SAWI AKIBAT PEMBERIAN PUPUK ORGANIK BIO-SLURRY DENGAN PENAMBAHAN NPK - Yulian Abdullah; Roosna M.O. Adjam (Politeknik Pertanian Negeri Kupang, 2017)
Fertilizing combination between organic and inorganic fertilizer can increase crop production because organic fertilizer improves physical, chemical, and biologicalcondition of the soil,hence give conducive circumstances to plant growth. The aim of the research was to identify the influence of the solid bio-slurry and NPK fertilizer on the growth and production of Brassica juncea L. The experimental design used in the study was Group Randomized Design (RBD) with 6 treatments and 4 replications to obtain 24 experimental units. The treatments were: P1: Bio-slurry 20 t.ha-1 + NPK 0 kg ha-1; P2: Bio-slurry 20 t.ha-1 + NPK 25 kg ha-1 +; P3: Bio-slurry 15 t.ha-1 + NPK 50 kg ha-1; P4: Bio-slurry 10 t.ha-1 + NPK 75 kg ha-1; P5: Bio-slurry 5 t.ha-1 + NPK fertilizer 100 kg ha-1; P6: Bio-slurry 0 t.ha-1 + NPK 125 kg ha-1. The results showed that the application of bio-slurry fertilizer with NPK gave effect to the growth and production of brassica, included plant heights, leaf numbers, fresh weights and dry weights of brassica at 28 day after plant of observation age. Keywords: Bio-slurry, mustard , organic fertilizer, NPK